Manajemen Pasar Tradisional Pasca Revitalisasi (Studi Kasus Di Pasar Hungayonaa Kecamatan Tilamuta Kabupaten Boalemo) - Namrud, Sukrianto; Lakoro, Fibriyanti S. (Ekopem: Jurnal Ekonomi Pembangunan, 2023)
The objectives of this study are (1) to determine the process of traditional market management after revitalization in Tilamuta District. (2) to find out the obstacles faced in the management of traditional markets after the revitalization in Tilamuta District. The research method used is descriptive qualitative. The types and sources of data used are primary and secondary. The data analysis technique carried out by the research is data analysis using the Miles and Huberman model which includes data reduction, data display and drawing conclusions and verification. The results of the research and discussion are (1) The management of the Tilamuta traditional market has not been supported by the existing equipment. (2) Post-Revitalization Tilamuta traditional market management is still limited to production and marketing. (3) The management of the Tilamuta traditional market after the revitalization is still not optimal in terms of development and maintenance. (4) The management of the Tilamuta traditional market after the Revitalization is still less than optimal because the market manager does not have the authority to set levies.